2010
DOI: 10.1016/j.febslet.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of p53 and its homolog p73 by protoporphyrin IX

Abstract: Edited by Varda RotterKeywords: p53 p73 Protoporphyrin IX Photodynamic therapy Fluorescent band shift Fluorescence polarization a b s t r a c tThe p53 tumor suppressor is recognized as a promising target for anti-cancer therapies. We previously reported that protoporphyrin IX (PpIX) disrupts the p53/murine double minute 2 (MDM2) complex and leads to p53 accumulation and activation of apoptosis in HCT 116 cells. Here we show the direct binding of PpIX to the N-terminal domain of p53. Furthermore, we addressed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…Kaeser reported in HCT116 colon carcinoma cells that PpIX is able to bind p53 (39). Later, Zawacka-Pankau et al showed that in cultured cells , PpIX binds to p53 at its N-terminus and disrupts the interaction between p53 and HDM2 (the human homologue of MDM2), thereby disrupting HDM2’s negative regulation of p53 (28, 40). If this scenario were operative in a given tumor cell, then a positive feed-forward loop might amplify 5-FU’s proapoptotic effect, since elevated PpIX (caused by altered heme enzyme expression in 5FU-pretreated cells) would bind to p53, stabilize it, and thereby increase p53’s ability to promote apoptosis after PDT damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaeser reported in HCT116 colon carcinoma cells that PpIX is able to bind p53 (39). Later, Zawacka-Pankau et al showed that in cultured cells , PpIX binds to p53 at its N-terminus and disrupts the interaction between p53 and HDM2 (the human homologue of MDM2), thereby disrupting HDM2’s negative regulation of p53 (28, 40). If this scenario were operative in a given tumor cell, then a positive feed-forward loop might amplify 5-FU’s proapoptotic effect, since elevated PpIX (caused by altered heme enzyme expression in 5FU-pretreated cells) would bind to p53, stabilize it, and thereby increase p53’s ability to promote apoptosis after PDT damage.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of p53 R273H, it was recently reported that the protein actually has antiapoptotic and antiautophagic activities, with tumors becoming even more resistant to cell death (44, 45). A paper by Sznarkowska et al suggests another possibility, namely, that cell death can be regulated by p73 (a p53 homolog that is rarely mutated in cancers and that binds to PpIX through its N-terminal domain, presumably stabilizing it (40). …”
Section: Discussionmentioning
confidence: 99%
“…77 TA isoforms of p53 family members has been shown to recognize the same target genes as p53 and work together to trigger apoptosis upon DNA damage. 79 Our thorough analysis in HCT116 p53 −/− cells manifests accumulation of apoptotic effectors Bak and PUMA, which in consequence leads to induction of cell death. 70 Our reports indicate that PpIX similarly to p53, binds to transactivation domain of p73.…”
Section: P53 Family Members and Their Role In Photodynamic Therapy Ofmentioning
confidence: 95%
“…In general, cancers having wild-type p53 are more sensitive to radio and chemotherapy in comparison to tumors which have mutated or deleted phenotype of p53 protein. Cellular stress induces stabilization of p53 and promotes, depending on the stress level, cell cycle arrest or apoptosis in the irreversibly damaged cells [30]. In this experiment, wild-type p53 cells were significantly more sensitive to oxidative stress mediated by Photofrin® under irradiation with 650 nm light, than cells expressing mutant p53, although uptake of the photosensitizer was equivalent for both studied CRC cell lines.…”
Section: Effect On Molecular Regulatory Factorsmentioning
confidence: 87%
“…terminal domain of p73 in vitro for the first time. These results suggest that PpIX disrupts the p53/MDM2 (murine double minute 2) or MDMX and p73/MDM2 complexes and thus activates the p53-or p73-dependent cancer cytotoxicity [30]. In order, Zawacka-Pankau and coworkers wondered if PpIX can activate p53 and induce cell death in a p53-dependent manner.…”
Section: Effect On Molecular Regulatory Factorsmentioning
confidence: 95%